Sistem Informasi Digital dan Pencari Jalan - Lisna Sukmawati; Jaswandi .; Adidin Aidin Maulana; Abdul Rahman (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
Generally new students and new visitors in a building often experience difficulties when searching for a space, especially a building that has a lot of space. As well as having a complex space, both classrooms and staff workspaces. Usually visitors who have just entered the building's environment ask the security information parties or other visitors to provide information on classrooms or staff workspace sought. Another way for visitors to find information on conventional building space is available, but the alternative method requires a lot of time. For this reason, this study was made in the campus building, using NetBeans IDE software applying the closest path search algorithm based on the pixel index value on the map image. The system will display the closest landing map and information on the lecturer room staff room and lecture classrooms and search for lecturer data information. Likewise the search for staff and lecturers by writing their names in the search panel on the touch screen monitor. then pressing the